The Influence of the Personality of Lecturers on Student Spiritual Improvement at STT Sola Fide Medan - Sampitmo Habeahan; Maniur Banjar Nahor; Heryanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the Influence of The Personality of Lecturers on Student Spiritual Improvement at STT Sola Fide Medan. The method used is descriptive method with quantitative studies. The descriptive method is a problem-solving procedure that is investigated by describing or describing the current state of the subject or object of research, based on facts or appearances as they are. The research was conducted at Sola Fide Theological High School Medan, Jalan Bunga Ncole D'Gardenia Housing Complex No.4, 5, 6 Medan City. The results showed that there was an effect of the lecturer's personality on increasing the spiritual attitude of students at STT Sola Fide Medan in 2021. That the personality of the lecturer had a significant influence on increasing the spiritual attitude of students at STT Sola Fide Medan in 2013.